The Integration of Fundamental and Technical Analysis in Predicting the Stock Price - isnaini nuzula agustin (Jurnal Manajemen Maranatha, 2019)
Fundamental Analysis and Technical Analysis have long been used by investors as an analysis instrument to predict the stock price in gaining optimal return. The purpose of this study is to test the predictive ability of Fundamental Analysis and Technical Analysis model partially, then simultaneously test the integrated model of both analysis. The scope of this study includes the listed companies in LQ 45 stock exchange during 2007- 2016 period. The Fundamental Variable used in this study are Earning per Share (EPS), Dividend Payout Ratio (DPR) and Return on Equity (ROE). The Technical Variable used is the price during the previous six months ( price t-0.5), Positive extreme price increase (D-Up), and Negative extreme price decline momentum (D-Down). The result of this study shows that Technical Model produces highest predictive ability compared to the other two models, while Integration model produces higher predictive ability compared to fundamental model. Using Integration model, EPS variable affects positively and significant, DPR variable affects negatively and insignificant, ROE variable, t-0.5, and D-Up affect positively and significant, while variable D down affects negatively and insignificant to the Stock Price. This result indicates that investors need to combine both analysis models i.e. fundamental and technical to generate optimal stock returns. Keywords and phrase : Earning Per Share, Dividend Payout Ratio, Extreme Positive Momentum, Extreme Negative Momentum.